Implementasi PMK 59 Tahun 2022 atas Pajak Belanja Barang pada Dinas PUPR Kabupaten Sambas - Mukaromah, Lailatul; Zurmansyah, Ee; Roshani, Roshani; Ramadhani, Gea Putri (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The obstruction of the ITA 22 collection process at the Public Works and Spatial Planning Office of Sambas Regency occurs due to field errors in the calculation of ITA 22 on transaction documents submitting payments for transactions carried out and reporting carried out by the PUPR Office manually through the Regional Finance Agency. This study aims to determine the procedures for calculating, depositing, and reporting Income Tax Article 22 on goods expenditure at the PUPR Office of Sambas Regency and to determine the application of calculating, depositing, and reporting tax on goods expenditure at the PUPR Office of Sambas Regency whether it is in accordance with PMK Number 59 of 2022. this research method is qualitative. Data collection conducted in this study through observation, interviews, and documentation. The focus of this research is the mechanism of calculation, deposit, and reporting of Income Tax Article 22 at the Public Works and Spatial Planning Office of Sambas Regency. The results obtained in this study can be concluded that the Sambas Regency Public Works and Spatial Planning Office has calculated and deposited Income Tax Article 22 in accordance with Permenkeu Number 59 of 2022 while for reporting it is not in accordance with Permenkeu Number 231 of 2019 but with a reconciliation system with the Sambas Regency Regional Finance Agency in collaboration with KPP Pratama Singkawang.